Biomedical Ontologies: Toward Scientific Debate - Maojo, V.; Crespo, J.; Garcia-Remesal, M.; de la Iglesia, D.; Pérez-Rey, D.; Kulikowski, C. (Methods of Information in Medicine, 2011)
Objectives: Biomedical ontologies have been very successful in structuring knowl edge for many different applications, receiving widespread praise for their utility and potential. Yet, the role of computational ontologies in scientific research, as opposed to knowledge management applications, has not been extensively discussed. We aim to stimulate further discussion on the advantages and challenges presented by biomedical ontologies from a scientific perspective.Methods: We review various aspects of biomedical ontologies going beyond their practical successes, and focus on some key scientific questions in two ways. First, we analyze and discuss current approaches to improve biomedical ontologies that are based largely on classical, Aristotelian ontological models of reality. Second, we raise various open questions about biomedical ontologies that require further research, analyzing in more detail those related to visual reasoning and spatial ontologies.Results: We outline significant scientific issues that biomedical ontologies should consider, beyond current efforts of building practical consensus between them. For spatial ontologies, we suggest an approach for building “morphospatial” taxonomies, as an example that could stimulate research on fundamental open issues for biomedical ontologies.Conclusions: Analysis of a large number of problems with biomedical ontologies suggests that the field is very much open to alternative interpretations of current work, and in need of scientific debate and discussion that can lead to new ideas and research directions.
Keywords: Biomedical ontologies; biomedical informatics; spatial ontologies; artificial intelligence; mathematical morphology